2019
DOI: 10.1007/978-3-030-29930-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Training Deep Learning Models via Synthetic Data: Application in Unmanned Aerial Vehicles

Abstract: This paper describes preliminary work in the recent promising approach of generating synthetic training data for facilitating the learning procedure of deep learning (DL) models, with a focus on aerial photos produced by unmanned aerial vehicles (UAV). The general concept and methodology are described, and preliminary results are presented, based on a classification problem of fire identification in forests as well as a counting problem of estimating number of houses in urban areas. The proposed technique cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Discriminative models are used for predictions/ classifications, whereas generative models are used for synthesis/generation of data similar to the input data set. The use of generative data to train DL models is promising, with early attempts in agriculture indicating positive outcomes [16]. Discriminative models, focused on predictions of the precise number of targets in an image, i.e., counting, are employed herein.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Discriminative models are used for predictions/ classifications, whereas generative models are used for synthesis/generation of data similar to the input data set. The use of generative data to train DL models is promising, with early attempts in agriculture indicating positive outcomes [16]. Discriminative models, focused on predictions of the precise number of targets in an image, i.e., counting, are employed herein.…”
Section: Related Workmentioning
confidence: 99%
“…Compared to traditional techniques, such as Support Vector Machines and Random Forests, DL has demonstrated enhanced performance in classification and counting computer vision-related problems [15]. A preliminary effort in this direction can be found in [16], where real and synthetic data were used together to count the number of houses from aerial photographs acquired by unmanned aerial vehicles (UAVs).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, DL-based algorithms and architectures have proven to be superior in difficult classification tasks, as illustrated by Trung et al [55], Wang et al [56], and Bui et al [57]. DL methods trained on synthetic data have achieved satisfactory results on real data as well [58]. Barth et al [59] reported better classification results in the modelling of artificial conditions (training/testing on synthetic images or controlled lighting conditions) to improve the segmentation of the details of yellow pepper.…”
Section: And Cnn In Generic Object Detection In Agriculturementioning
confidence: 99%
“…The aforementioned datasets are presented in Table 3. Finally, in another paper [61], the dataset was a combination from web-searched images, with a proposed method of synthesized image datasets [62].…”
Section: Datasetsmentioning
confidence: 99%